Analysis of Kaligarang Fault Deformation with GNSS Survey in 2016-2018. (August 2019) - Awaluddin, M; Sabri, L M; Amarrohman, F J; Yuwono, B D; Nugraha, A L; Immanuel, L
Abstract: The GNSS Survey has been conducted for the deformation of Kaligarang Fault in 2016 and 2018. Active fault activity can be shown by the value of slip rate and locking depth. The magnitude of the slip rate cannot be measured directly, but the displacement on the surface of the earth data could be obtained from GNSS measurements. Then the slip rate could be calculated by inversion techniques from the displacement data form GNSS survey. We have done the slip rate modeling using the displacement data using the value of locking depth 5, 10, 15 and 15 km. But the position of the observation station point cannot converge to a single slip rate line at all locking depth values. Therefore this research has not been able to infer the optimal slip rate for Kaligarang fault.